Characteristics of white matter structural connectivity in healthy adults with childhood maltreatment. Issue 1 (31st December 2023) - He, Jiayue; Zhong, Xue; Cheng, Chang; Dong, Daifeng; Zhang, Bei; Wang, Xiang; Yao, Shuqiao
ABSTRACT: Background: Childhood maltreatment (CM) is a common psychological stressor associated with multiple mental disorders. While CM is associated with vulnerability to depression and anxiety, little is known about the specific mechanism underlying this relationship. Objective: This study aimed to investigate the white matter (WM) of healthy adults with CM and their relationships with depression and anxiety to provide biological evidence for the development of mental disorders in subjects with childhood trauma. Methods: The CM group included 40 healthy adults with CM. The non-CM group included 40 healthy adults without CM. Diffusion tensor imaging (DTI) data were collected, and tract-based spatial statistics (TBSS) were applied to the whole brain to assess WM differences between the two groups; post-hoc fibre tractography was used to characterise the developmental differences; and mediation analysis was used to assess the relationships among the Child Trauma Questionnaire (CTQ) results, DTI indices, and depression and anxiety scores. Results: Relative to the non-CM group, the CM group revealed significantly lower fractional anisotropy (FA) in the right posterior corona radiata (PCR-R), right anterior corona radiata (ACR-R), left super corona radiata (SCR-L), anterior thalamic radiation (ATR), and right posterior limb of the internal capsule (PLIC-R). Additionally, shorter fibre bundles passed through the PCR-R, ACR-R, and ATR in the CM group compared with the non-CM group. Besides, the length of the ACR-R mediated the relationship between CM and trait anxiety. Conclusions: The alteration of white matter microstructure associated with childhood trauma in healthy adults may reflect biomarkers of childhood trauma. Besides, an alteration of WM microstructure in healthy adults with CM mediates the association between CM and trait anxiety, which may represent the vulnerability to developing mental disorders after childhood trauma experiences. HIGHLIGHTS: In this paper, we found specific alterations associated with CM in healthy adults, which may mediate the relationship between childhood trauma and trait anxiety in later life.